An effectiveness of teamwork at the workplace and it's association with employee's job satisfaction / Ramlah Ismail - Ismail, Ramlah (2004)
Factors that influence the effectiveness of teamwork and job satisfaction can be the important driven to the organization's efficiency and effectiveness. It is because, different people feel in different way and levels of job satisfaction. Teamwork is the important way that can promote the satisfaction on jobs. Meaning that, the high degree of the effectiveness of teamwork can develop and sustain the organization's performances in which depend on how employees perceives towards fulfilling their job satisfaction. For that reason, these studies are examines the factors that will contribute to the level of job satisfaction among the employees at Totokiki (Malaysia) Sdn. Bhd. Besides of administered questionnaires and interviewing, other methods of research that have been applied in this study are data collection, cluster sampling technique, and also Statistical Package for Social Sciences (SPSS). Hopefully the finding can aid Totokiki (Malaysia) Sdn. Bhd to enhance their level of employee's satisfaction.